Production of Diverse Varieties of Amylolytic Starters In the North Bengal region For Sustainable Livelihood of Ethnic Tribes and Microbiology of Produced amylolytic Starters (International Journal of Food and Nutritional Sciences, 2022)
Fermentation is an integral part of ethnic people of North Bengal for the preservation of raw substrate from spoilage as well as to preserve the viable forms of microbial consortia for the desired food development. Ethnic communities prepare different types of fermented foods, alcoholic beverages and amylolytic starters by using their traditional knowledge. These fermented foods they consume and sell for their sustainable livelihood. There are different types of fermented foods and alcoholic beverage in North Bengal region prepared by these ethnic population from the ancient times. There are various types of alcoholic starters in the North Bengal region, prepared by using glutinous rice as raw substrate and old starter culture which contains the microbial inocula for the fermentation and final product development. These amylolytic starters contains yeasts, molds and lactic acid bacteria their microbial consortia and dominance of yeasts and molds have been observed. All eight district of North Bengal contains different types of alcoholic starters with different microbial diversity. The molds plays an important role in the breakdown of polysccharides to disaccharides and yeasts plays an important role in the fermentation of monosachharides thereby producing alcohol and carbon di-oxide as final products and so the name alcoholic fermentation. Marcha, dabai, chot, and ranu goti, are traditionally prepared dried amylolytic starters used to produce various ethnic alcoholic beverages in this region. In the present study the phenotypic characterization gives the metabolic fingerprints of yeasts present in all alcoholic starters of North Bengal samples which showed major dominance of (yeasts). Scanning electron microscope (SEM) has been performed to reveal the surface structures of yeast isolates. The alcohol content of the fermented product ranges between from 6-6.5 %, and the alcohol tolerance is up to 17 % (v/v), pH ranges between 3.9 to 4.0. The present study reveals the microbial diversity among diverse variety of all eight types of alcoholic starters from eight districts of North Bengal as well traditional production process of alcoholic starters in all eight districts and how it promote sustainable livelihood of ethnic people in this region.